The Influence of Transformational Leadership and Work Motivation on Employee Performance: Study at One of The Hotels in Bandung - Handayani Hamidah Fauji; Adhie Fasha Nurhadian (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This research is motivated by the significant competition between construction service providers in the Civil Water sector. This research was carried out in Bandung to learn about and analyze transformational leadership and communication on employee performance in one of the companies operating in Bandung's architectural, civil, mechanical, electrical, and environmental management consulting services. Employee performance generally focuses on transformational leadership and communication. The research method used is quantitative, with a descriptive and verification approach. The sample used was 100 employees at a company engaged in architectural, civil, mechanical, electrical, and environmental management services in Bandung. The research results show valid results for each statement item with a value of 0.3, and reliable results show a value above 0.7. For transformational leadership, (X1) is 0.784, Communication (X2) is 0.789, and Employee Performance (Y) is 0.780. From the value (R Square), it is known that the influence of transformational leadership (X1) and communication (X2) on employee performance (Y) is 0.810 or 81.0%. Leadership (X1), Communication (X2), and Employee Performance (Y) are in the relatively good category. The direct influence of transformational leadership (X1) is 13.3%. The direct influence of Communication (X2) is 32.1%. Employee performance is influenced by transformational leadership and communication by 81.0%, while the remaining 19.0% is caused by other variables or other factors that were not researched. From the research results above, it can be concluded that transformational leadership and communication significantly influence employee performance in one of the companies operating in the architectural, civil, mechanical, electrical, and environmental management consulting services in Bandung. The practical implications of these findings are that professionals in this field can enhance employee performance by adopting transformational leadership and effective communication strategies.